(untitled) (Research, Society and Development, 2022)
The objective of this work was to study the biometrical characteristics and predation of H. parvifolia Huber seeds. It was measured the length, width and thickness of the seeds and the number of seeds per fruit and fresh mass of seed. For intact seeds and predated seeds it was measured the percentages and index speed of germination. The length, width and thick of the fruit were 8,5 cm, 4,1 cm and 3,2 cm, respectively. The fruits had 3,9 seed/fruit and the percentage of damaged seeds by insects (33,1%) was high. The predated seeds had germination percentages of 3,8% and index speed of germination of 0,0328 day-1. Rhinochenus stigma (L.) (Coleoptera: Curculionidae) affected is an important damageof H. parvifolia Huber seeds.